Impact of education on quality of life of laryngectomized patients before and after vocal rehabilitation - Mila Bunijevac; Mirjana Petrović-Lazić; Siniša Maksimović (Биомедицинска истраживања, 2019)
Introduction: Larynx carcinoma is one of the most common malignant tumors of the upper aerodigestive tract that causes the change in normal anatomical relationships in the neck, which leads to communication and social interaction disorders. The aim of the paper is to examine the impact of education on the quality of life of laryngectomized patients. Methods: The study included 50 laryngectomized patients, aged 51 to 83 years. The subjective voice assessment was carried out using the Voice Handicap Index (VHI) and the University of Michigan Head & Neck Quality of Life Instrument (HNQOL). The patients filled in the questionnaires before and after vocal rehabilitation. Results: The comparison of average scores of all examined laryngectomized patients before and after vocal rehabilitiation showed a statistically significant difference in the total score on VHI scale (107.20 ± 8.46 vs. 21.32 ± 13.29; p < 0.001), HNQO scale (52.50 ± 17.71 vs. 93.57 ± 6.36; p < 0.001), as well as on all subscales. Prior to vocal rehabilitation, there was no statistically significant difference between the scores on these two scales in patients with different level of education. After vocal rehabilitation, there was a statistically significant difference between the patients with secondary education and the ones with tertiary education in the scores on all VHI subscales, and total VHI score (23.60 ± 13.54 vs. 18.83 ± 11.59; p = 0.012), as well as in the scores for individual domains and the total score of HNQOL instrument (88.90 ± 6.58 vs. 99.80 ± 4.25; p = 0.048). Conclusion: Vocal rehabilitation after total laryngectomy had a positive effect on patients' quality of life, and patients with higher education showed a tendency towards better quality of life compared to the ones with lower education.
Keywords: total laryngectomy; education; vocal rehabilitation; quality of life